Numerical modelling of bidirectional dry gas face seals - Ojile, Joel Oroh (Cranfield University, 2009)
The optimization of the geometrical parameters of the aerodynamic lift features and the analysis of the fluid flow in the seal interface are inter-twined. Any small changes in the geometrical parameters of the aerodynamic lift features significantly affect the performance of a non-contacting gas face seal. For a gas face seal to function with optimum performance requires that the optimum geometrical parameters be identified. This can be achieved through a lengthy trial and error process, often heavily dependent on the designer’s depth of insight, itself dependent on experience, or can be achieved through automated numerical methods. The purpose of this research was to develop a reliable numerical model that can serve as a design tool for simulating the performance of both unidirectional and bidirectional dry gas face seals. This was achieved in three steps. The first approach consisted in developing a 2D numerical model that employed the Reynolds equation for seals operating at very low rotating speeds and low pressure differentials. In the second step a 3D-CFD model was assembled and the practicability of using CFD, in a seal design loop, for seals operating in wide range of operating conditions, was investigated. This model employed a commercial CFD package (ANSYS CFX version 11). For last approach both models were incorporated into an automatic optimization tool that can generate optimal seal geometries with a minimum of human intervention. An extensive set of results from the analysis of dry gas face seals spanning across different operating conditions and geometrical seal face profiles, with the inclusion of convergent radial taper, are presented and discussed in this thesis. The results obtained from the Reynolds equation and 3D CFD models are compared and critically analysed. Results obtained with both models are validated against test data obtained from AESSEAL plc, the sponsor of this research. The 3D CFD model predictions showed a better agreement with the test data on the seal leakage than the Reynolds equation model. The leakage rates and fluid film thickness predictions illustrate how the 3D CFD model can be used for seal design while overcoming some of the shortcomings of the Reynolds equation based models. The major limitation of the 3D CFD model is that it is computationally expensive. An automatic optimization tool which can be used for the design of dry gas face seals has been presented. The improvements achieved from the optimization of a spiral groove face seal utilising the automatic optimization tool are: 4.8% increase of opening force, 13.2% reduction of seal leakage, 20.7% increase of design efficiency parameter, 28.3% increase of axial film stiffness and 15.9% reduction of power consumption. A proposed new design of dry gas face seal capable of bidirectional operation has been presented. This type of seal outperformed the spiral groove face seal, in reverse rotation of the sealing shaft, in terms of opening force and positive axial film stiffness.